Production of bioethanol from pretreated water hyacinth (Eichhornia crassipes (Mart.) solms) by Saccharomyces cerevisiae - Harun, Mohd Yusof (2011)
In this work, potential of producing bioethanol from water hyacinth plant (Eichhornia crassipes) was investigated with emphasis on (1) selecting physical pretreatment method for treating raw water hyacinth biomass, (2) optimization of dilute acid hydrolysis of water hyacinth biomass, and (3) evaluating the fermentation of water hyacinth acid hydrolysate using Saccharomyces cerevisiae. Effects of physical pretreatments (drying, grinding, boiling, steaming, uItrasonication and combination) on water hyacinth were assessed from sugar yield in hydrolysis and biomass morphological changes. Untreated water hyacinth had produced 24.69 mg sugar/g dry matter. Among all test conditions, dried and pulverized sample had liberated the highest amount of sugar in hydrolysis (155.13 mg sugar/g dry matter). Hydrolysis time was reduced up to 38% when using pretreated samples. Morphology images and thermal analysis showed disruptions of plant structure on pretreated biomass. Five parameters were tested in optimization of dilute acid hydrolysis of water hyacinth using Response Surface Methodology, namely temperature (l00°C - 120°C), acid concentration (0.5 %v/v - 5.0 %v/v). processing time (30 minutes - 120 minutes), solid loading (I %w/v - 5 %w/v) and reaction volume (10 ml - 50 ml). Screening experiments revealed that the first three parameters have significant effects on the studied process and these variables were subjected to optimization experiments using Box-Behnken design. From several statistical analyses, a model to explain the studied process was proposed and an optimal process setting to maximize sugar yield was determined. High R2 (97.1 %) and low AAD (3.06%) values of the model indicates good agreements between the experimental and theoretical data. Detoxification of acid hydrolysate to remove luran derivatives and organic acids content was carried out by overliming using NaOH (2M) at different pH (9, 10 and II) and holding time (15, 30 and 45 minutes). a sisted with mild heating at 60°C. Suuar loss and removal of furan derivatives and organic acids were recorded as a I::> basis for selecting detoxified hydrolysates for fermentation test using Saccharomyces cerevisiac. Parallel fermentation using non-detoxified hydrolysate, synthetic hydrolysate and nutrient broth (control) were also conducted. Data on cell density and ethanol production during 48 hours of incubation were collected and analyzed. Sugar loss was detected in all test conditions with xylose being the most affected sugar. More than 90% of furan derivatives and organic acids contents were removed when hydrolysatcs was detoxified at pH 10 for 45 minutes and all conditions afterwards. Hydrolysate that was detoxified at overliming pH of II for 45 minutes displayed highest specific growth rate of Saccharomyces cercvisiae, 1.71 x 10-2 hr'l. and highest ethanol production, yp/s = 2.27 x 10-2 g ethanollg glucose. This study concludes that water hyacinth has the potentials to be developed as future bioethanol source.